Target Values and Daytime Variation of Bone Turnover Markers in Monitoring Osteoporosis Treatment After Fractures. (9th May 2022) - Borgen, Tove T; Solberg, Lene B; Lauritzen, Trine; Apalset, Ellen M; Bjørnerem, Åshild; Eriksen, Erik F
ABSTRACT: The serum bone turnover markers (BTM) procollagen type 1 N‐terminal propeptide (P1NP) and C‐terminal cross‐linking telopeptide of type 1 collagen (CTX) are recommended for monitoring adherence and response of antiresorptive drugs (ARD). BTM are elevated about 1 year after fracture and therefore BTM target values are most convenient in ARD treatment follow‐up of fracture patients. In this prospective cohort study, we explored the cut‐off values of P1NP and CTX showing the best discriminating ability with respect to adherence and treatment effects, reflected in bone mineral density (BMD) changes. Furthermore, we explored the ability of BTM to predict subsequent fractures and BTM variation during daytime in patients using ARD or not. After a fragility fracture, 228 consenting patients (82.2% women) were evaluated for ARD indication and followed for a mean of 4.6 years (SD 0.5 years). BMD was measured at baseline and after 2 years. Serum BTM were measured after 1 or 2 years. The largest area under the curve (AUC) for discrimination of patients taking ARD or not was shown for P1NP <30 μg/L and CTX <0.25 μg/L. AUC for discrimination of patients with >2% gain in BMD (lumbar spine and total hip) was largest at cut‐off values for P1NP <30 μg/L and CTX <0.25 μg/L. Higher P1NP was associated with increased fracture risk in patients using ARD (hazard ratio [HR]logP1NP = 15.0; 95% confidence interval [CI] 2.7–83.3), p = 0.002. P1NP and CTX were stable during daytime, except in those patients not taking ARD, where CTX decreased by 21% per hour during daytime. In conclusion, P1NP <30 μg/L and CTX <0.25 μg/L yield the best discrimination between patients taking and not taking ARD and the best prediction of BMD gains after 2 years. Furthermore, higher P1NP is associated with increased fracture risk in patients on ARD. BTM can be measured at any time during the day in patients on ARD. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. Abstract : Daytime variation of (A) procollagen type 1 N‐terminal propeptide (P1NP) and (B) C‐terminal cross‐linking telopeptide of type 1 collagen (CTX) in patients using antiresorptive drugs (ARD) (yellow dots) and in patients not using ARD (blue triangles).